The tendency to migration of eldery people inhabitants of big cities - Kałuża-Kopias, Dorota (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Poland’s population is aging like the populations in most developed countries. The fast rising number of the oldest old (the so‑called “double aging”) and their problems will probably be the dominant theme in the debate about seniors in coming decades. The purpose of this paper is to present the potential motives of migration of people over the age of 75 residents of large cities in Poland. Performed material from their own research that has been carried between February and August 2016. The analysis results indicate that older people are reluctant to change their place of residence, and the main theme of migration are health problems.